SIMBOL NILAI-NILAI KEARIFAN LOKAL DALAM DOLANAN ANAK SURABAYA PADA BUKU PRÈJÈNGANÉ KUTHO SUROBOYO - Yeni Rakhmawati Agustin; Adelia Savitri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research aims to explore the symbols of local wisdom values in Surabaya children’s games featured in the book Prèjèngané Kutho Suroboyo. Traditional games serve not only as a means of entertainment but also as a medium for transmitting cultural values and social norms that have been passed down from generation to generation. This study employs a qualitative descriptive method using Charles Sanders Peirce’s semiotic approach. The research data source is the book *Prèjèngané Kutho Suroboyo*, which contains children’s games from Surabaya. Data collection techniques were conducted through reading, note-taking, and documentation. Data analysis was conducted by examining the triadic relationship between the representamen, object, and interpretant to uncover the meaning of the signs found in these traditional games. The results of the study indicate that the games èngklék, Jang Jing Si Pengusir Anak Kèpèt, bèntèng-bèntèngan, and jumping rope contain various values of local wisdom, namely togetherness, mutual,sportsmanship, discipline, patience, courage, perseverance,group loyalty, heroism, cleanliness, harmony, agility,strategy, and resilience. These values are represented through game movements, interactions among players, and symbols found in each game. This study concludes that the traditional games of Surabaya serve as cultural symbols that play a role in character development as well as the preservation of the community’s local wisdom.